Dacryoadenitis with Ptosis and Diplopia as the Initial Presentation of Granulomatosis with Polyangiitis - Hibino, Makoto (Intern Med, 2017)
A 77-year-old Japanese woman presented to an ophthalmologist with an erythematous swollen upper eyelid and diplopia which was initially diagnosed to be idiopathic dacryoadenitis on the basis of a histological evaluation of an orbital mass that was in remission following a 3.5-month period of systemic corticosteroid therapy. She subsequently developed respiratory symptoms, and was finally diagnosed with systemic granulomatosis with polyangiitis (GPA) based on the clinical and histological features. She was successfully treated with corticosteroids and azathioprine. Dacryoadenitis in the form of an orbital inflammatory pseudotumor may be an initial presenting feature of GPA, sometimes as the limited phenotype, and occasionally progressing to systemic disease.